INFESTASI CACING PADA SAPI POTONG PEMELIHARAAN INTENSIF DI KABUPATEN SLEMAN YOGYAKARTA - Widodo Suwito (Scripta Biologica, 2018)
Worm infestation in cow is economically disadvantageous such as inhibited the body growth, decrease milk production, and reduce the fertility. The aim of the current study was to determine type of infestation worm in cow which communal cage in Cageran, Taman Martani, Kalasan, Sleman and its relationship with type of feed and cleanliness on the floor cage. The samples were collected from faeces calves (n=25), cow (n=38), and bull (n=20). The samples were identified against worm eggs based on the morphology and size. The bivariate analysis chi square (χ2), odds ratio (OR), and relative risk (RR) were used to relationship worm infestation with feed type and cleanliness floor of the cage. Fasciola sp, Strongyl sp, and Ascaris sp are type of worm infestation in calves, cow, and bull. The Fasciola sp, is most founding in calves (n=10), cow (n=19), and bull (n=15), while Strongyl sp, and Ascaris sp are rarely. The feed of rice straw is association with fasciolosis in calves (χ2:6,25;OR:13,05;RR:2,33), cow (χ2:10,25;OR:8,25;RR:5,93), and bull (χ2:11,05;OR:5,13;RR:3,13). Association between cleanliness floor of the cage with infestation Fasciola sp, Strongyl sp, and Ascaris sp are (χ2:5,36;OR:12,31; RR: 3,28) in calves, cow (χ2:4,13;OR:3,31;RR:3,28), and bull (χ2:3,96;OR:1,17;RR:1,81). The study showed that Fasciola sp, is most widely worm infestation in calves, cow, and bull in communal cage in Cageran, Taman Martani, Kalasan. Feed of rice straw is potential causes of the Fasciola sp and cleanliness floor of the cage is more importance to prevent the worm infestation in calves, cow, and bull.